(untitled) (Comprehensive Journal of Science, 2025)
This research addresses the principle of meritocracy in public office appointments under Libyan law. Its aim is to clarify the concept of meritocracy, its legal basis, and the principles upon which it rests. To achieve this, the research is divided into two sections and two subsections. The first section discusses the concept and definition of meritocracy and its legal basis. The second section addresses the principles upon which meritocracy rests in public office appointments, namely the principles of equality and equal opportunity, and is further divided into two subsections